Measuring turbulence in a flotation cell using electrical resistance tomography. (14th October 2015) - Meng, Jun; Xie, Weiguo; Runge, Kym; Bradshaw, Dee
Abstract: Measuring turbulence in an industrial flotation environment has long been problematic due to the opaque, aggressive, and abrasive three-phase environment in a flotation cell. One of the promising measurement techniques is electrical resistance tomography (ERT). By measuring the conductivity distribution across a measurement area, ERT has been adopted by many researchers to monitor and investigate many processes involving multiphase flows. In the research outlined in this paper, a compact ERT probe was built and then used to measure the conductivity distribution within a 60 l flotation cell operated with water and air. Two approaches were then developed to process the ERT data and estimate turbulence-related parameters. One is a conductivity variance method and the other is based on the Green–Kubo relations. Both rely on and use the fluctuation in the ERT measurement caused by bubbles moving through the measurement area changing the density of the fluid. The results from both approaches were validated by comparing the results produced by the ERT probe in a 60l flotation cell operated at different air rates and impeller speeds to that measured using an alternative turbulence measurement device. The second approach is considered superior to the first as the first requires the development of auxiliary information which would not usually be known for a new system.